ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA PT. MULTI MAS CABANG PEKANBARU - Asrida, Neli (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
The goal of this research to know the influence of quality and service quality on customer loyalty. Sampel of this research is 76 customer PT. Multi Mas Pekanbaru in Rokan Hulu and a informan is fertilizer distributor who has long worked in the PT. Multi mas Pekanbaru branch who has know about the quality of products and service quality that has been given by PT. Multi Mas Pekanbaru Branch. The data obtained from questioners and interviews, the data from quetioners processed using SPSS 21 and descriptive analyzed through interviews with informan.The result of this research in accordance with the T test to variabel quality of the product obtained by comparison of the calculated value T = 7.133 > t tabel = 1.993, in order to there is a significant influence product quality to customer loyalty as well as test results T to variabel quality of service obtained result of comparison of the value of T = 8.950 > t tabel = 1.985 so that there is a significant influence of service quality on loyalty